Development of an energy-efficient intelligent battery charger - Ho, Yeong Khing. (2008)
A battery charger/management system was developed to cater for the simultaneous charging of three batteries, each with different capacity, and requiring different charging parameters. Each battery, with a unique identity code, has a history file associated with it.